PERSEPSI GURU TERHADAP IMPLEMENTASI KURIKULUM MERDEKA DALAM KONTEKS PENDIDIKAN GURU SEKOLAH DASAR DI SD NEGERI KUASAET KOTA KUPANG - Nubatonis, Yunita; Koroh, Taty R.; Bulu, Vera R. (SINERGI : Jurnal Riset Ilmiah, 2025)
This research is based on the lack of perception of teachers of SDN Kuasaet Nusa Tenggara Timur, Maulafa District, Kupang City towards the implementation of the independent curriculum, this is shown by the low understanding of teachers related to information technology which is in contrast to the independent curriculum which requires teachers to be creative, innovative, and able to adapt to the increasingly demanding conditions of the               times so that more creative learning is created. Therefore, the purpose of this study is to find out teachers' perceptions of the implementation of the independent curriculum in the context of elementary school teacher education at SD Negeri Kuasaet, Kupang City. The type of research used in this study is qualitative descriptive research with data collection techniques in the form of observation, interviews and documentation studies while the data analysis is carried out by interactive data analysis techniques which include data reduction, data display, conclusion and verification. The research subjects in the study were 6 teachers and principals at SDN Kuasaet.  The results of the study show that in the implementation of the independent curriculum at SDN Kuasaet there are several obstacles including the lack of training, limited technological understanding, and obstacles in adapting to curriculum changes, but related to teachers' perception of the implementation of the independent curriculum in the context of education at SD Negeri Kuasaet in Kupang city has received a positive response from all teachers which is evidenced by how they see the independent curriculum as an opportunity for a dynamic learning experience, and many teachers have successfully adapted to the approach that exists in their curriculum.